Effect of Earning Assets, Liquidity, and Equity on Profitability and Company Value at State-Owned Banks Listed on the Indonesia Stock Exchange 2009-2018 - Mutmainna Amalia; Syamsu Alam; Erlina Pakki (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
The research was conducted at state-owned banks listed on the Indonesia Stock Exchange for the period 2009-2018. The focus of the study is the firm value (Y2) with the predictor variable earning asset quality (X1), liquidity (X2), and equity (X3) with the intervening variable profitability (Y1). Used secondary data obtained from documentation by sample companies and also the Indonesian Financial Services Authority. The data analysis technique used path analysis. The purpose of this study was to examine the direct effects of X1, X2, X3 on Y1 and Y2 and to examine the indirect effects of X1, X2, X3 on Y2 through Y1. The results showed that X1, X2, X3 had a direct and significant positive effect on Y1, and X1, X3, Y1 had a significant positive effect directly on Y2. While X2 has no significant effect on Y2, but still has a positive direction. This is due to the liquidity risk borne by the bank and affects the net profit after tax. For the indirect effect, the results obtained by X1, X2, X3 have no significant effect on Y2 through Y1. The use of capital structures with high costs weakens the indirect relationship of each variable.